2020
DOI: 10.3389/fphy.2020.00343
|View full text |Cite
|
Sign up to set email alerts
|

Generation of α-Particle Beams With a Multi-kJ, Peta-Watt Class Laser System

Abstract: We present preliminary results on generation of energetic α-particles driven by lasers. The experiment was performed at the Institute of Laser Engineering in Osaka using the short-pulse, high-intensity, high-energy, PW-class laser. The laser pulse was focused onto a thin plastic foil (pitcher) to generate a proton beam by the well-known TNSA mechanism which, in turn, was impinging onto a boron-nitride (BN) target (catcher) to generated alpha-particles as a result of proton-boron nuclear fusion events. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
0
27
1
Order By: Relevance
“…CR-39 films were set at 21 • and 138 • with respect to the laser direction and at 35.9 and 48.3 cm, respectively, from the target. Calibration of CR-39 was made at INFN [26] in Catania using a 241 Am thin source emitting α particles at 5.486 MeV (85.2%) and 5.443 MeV (12.8%) [7]. By introducing appropriate filters in front of the source, the energy of particles was degraded to 2.6 MeV.…”
Section: B Cr-39 Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…CR-39 films were set at 21 • and 138 • with respect to the laser direction and at 35.9 and 48.3 cm, respectively, from the target. Calibration of CR-39 was made at INFN [26] in Catania using a 241 Am thin source emitting α particles at 5.486 MeV (85.2%) and 5.443 MeV (12.8%) [7]. By introducing appropriate filters in front of the source, the energy of particles was degraded to 2.6 MeV.…”
Section: B Cr-39 Filmsmentioning
confidence: 99%
“…The proton-boron (p-B) fusion reaction has been investigated since the 1930s [1] and has received growing interest in recent years, due to multiple applications in different fields [2][3][4][5][6][7]. In the context of fusion for energy, this reaction has the advantage of releasing its energy with a very low neutron emission, which is attractive for the safety of a fusion reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a main resonance of such nuclear reactions occurring for incoming proton beam energies at 675 keV [1], which shows a corresponding cross-section of about 1.2 barn. The α-particles generated from p-B fusion present a broad energy spectrum that peaks around 4 MeV [1]; however, cutoff energies up to 10 MeV have been demonstrated experimentally [2][3][4][5][6]. In the last 15 years, p-B fusion has been effectively induced by means of high-power lasers, which has reported an impressive progression in the reaction yield [2,4,7,8], thus has become a point of interest for the energy sector where it is being considered as an alternative approach to conventional inertial confinement fusion schemes [9][10][11] and also potentially for medicine where intense α-particle beams can be used for radioisotope production [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, an extensive systematic investigation of laser-based p-B fusion of the deep understanding of the underpinning physics is still missing [13]. An overview of the recent experimental progression in p-B fusion in terms of α-particle flux (or flux per input laser energy) is shown in Figure 1, both for the "in-target" [2][3][4]7,14] and "pitcher-catcher" geometries [5,6,8,15]. In this work, we show the first experimental results of efficient α-particle production from p-B fusion using a PW-class laser in the "in-target" (i.e., direct irradiation) configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Activation is mainly induced by two sources: the X-rays produced by energetic electrons through the Bremsstrahlung process in thick targets made of a heavy element (source TS1) and the protons accelerated to high energies from thin targets made of light elements (source TS2). ese two kinds of targets, used for photon [10] and proton sources [11][12][13], shown in Figure 1, are commonly used in experiments for X-ray radiography [14], proton radiography [15], opacity measurements, target heating [16], and for producing nuclear reactions [17].…”
Section: Calculation Methodologymentioning
confidence: 99%